Repulsively induced photon superbunching in driven resonator arrays - Grujic, T; Clark, SR; Jaksch, D; Angelakis, D (2013)
We analyze the nonequilibrium behavior of driven nonlinear photonic resonator arrays under the selective excitation of specific photonic many-body modes. Targeting the unit-filled ground state, we find a counterintuitive "superbunching" in the emitted photon statistics in spite of relatively strong on-site repulsive interaction. We consider resonator arrays with Kerr nonlinearities described by the Bose-Hubbard model, but also show that an analogous effect is observable in near-future experiments coupling resonators to two-level systems as described by the Jaynes-Cummings-Hubbard Hamiltonian. For the experimentally accessible case of a pair of coupled resonators forming a photonic molecule, we provide an analytical explanation for the nature of the effect. © 2013 American Physical Society.